Abusive Supervision and Withdrawal Behaviors: Defensive Role of Ability-Job-Fit - Bhattarai, Ganesh; Pokhrel, Dhruba Raj; Dahal, Rewan Kumar; Sharma, Sumedha (Saptagandaki Journal, 2020)
Researchers concentrated on antecedents and consequences of abusive supervision and paid less attention to factors that mitigate abusive supervision’s harmful effect in an organization. As a response to the situation, this study was carried out to measure the (i) direct impact of abusive supervision on withdrawal behavior, (ii) direct impact of ability-job-fit on withdrawal behavior, and (iii) defensive role of ability-job-fit for the harmful effect of abusive supervision on withdrawal behavior. Perceptual data were collected from the 350 employees working in the Nepalese multipurpose saving and credit cooperative limited. To infer the conclusion, data were analyzed quantitatively adopting the deducting reasoning approach and positivist research philosophy. This study found that there was- a positive impact of abusive supervision on withdrawal behaviors, negative impact of ability-job-fit on withdrawal behaviors, ability-job-fit defended the harmful effect of abusive supervision on withdrawal behavior. Moreover, abusive supervision’s harmful effect on withdrawal behaviors was less for those who perceived high ability-job-fit and vice versa. Numbers of practical and theoretical implications are suggested.